Morphology of the Patellar Tendon and the Contractility Response of the Quadriceps: Symmetry and Gender Analysis - Abián, Pablo; Martínez, Fernando; Jiménez, Fernando; Abián-Vicén, Javier (International journal of environmental research and public health, 2021)
The purpose of the study was to describe the differences between the dominant and non-dominant leg regarding contractility response and quadriceps strength and the morphology and stiffness of the patellar tendon (PT) in a group of physically active men and women. Fifty physically active subjects (36 men and 14 women) were evaluated for morphology and stiffness of the PT, contractility response of the rectus femoris of the quadriceps, isometric strength of the quadriceps and hamstrings, and isokinetic strength (concentric and eccentric) at 60°/s of the knee extensors. The measurements were made on the subject’s dominant and non-dominant leg. The men showed a greater thickness of the PT in both legs compared to the women. Regarding the contractility response, the women recorded a 10.1 ± 16.2% (p = 0.038) greater contraction time (ct) in the dominant versus the non-dominant leg and the men recorded 11.9% (p = 0.040) higher values in the dominant leg compared to the women. In all the absolute strength measurements the men recorded higher values (p < 0.05) than the women, however, when the values were normalised with respect to the muscle mass of the leg these differences disappeared. The dominant leg showed values of isometric strength and eccentric strength at 60°/s (p < 0.05) greater than the non-dominant leg. The reference values provided in this study of the knee extensors and PT may be useful for detecting possible muscular or tendinous anomalies.